(untitled) (Chemical Engineering Research Bulletin, 2023)
Plastics are a menacing threat to the environment. As a substitute for synthetic plastics, biodegradable alternatives can mitigate the pollution problem. Cellulose is one of the natural ingredients in biodegradable plastic production. Water hyacinth (WH), a prolific aquatic weed abundant in cellulose, can be exploited for this purpose. The aim of this study was to extract cellulose from WH, to fabricate biodegradable plastic films using WH cellulose in different proportions with starch and to compare the properties of the samples. To isolate cellulose, sun-dried WH powder was bleached with H2O2 and alkalized with NaOH. Cellulose powder thus obtained was used to develop several bioplastic films, by mixing with arrowroot starch in different proportions, as well as acetic acid and glycerol. The mixture was gelatinized and molded into thin films. The plastics possessed satisfactory homogeneity, water absorption capacity, tensile strength, heat-sealability and were biodegradable. It was also observed that incorporation of cellulose powder to a certain extent contributed to improved properties of the bioplastic. Chemical Engineering Research Bulletin 23 (2023): 79-83